Anti-Hepatitis C Activity of Combination of Ruta angustifolia Extract and Ribavirin - Tutik Sri Wahyuni; Adita Ayu Permatasari; Chie Aoki-Utsubo; Aty Widyawaruyanti; Achmad Fuad (Universitas Airlangga, 2022)
Background: Hepatitis c virus infection is a global health problem which chronically infected 71 million people in the world. This infection has a risk of becoming liver cirrhosis and hepatocellular carcinoma. Since the current HCV therapy has been developed by direct-acting antivirals (DAA), however, most patients get limited access due to the high cost. Therefore, further development anti-HCV agent still greatly needed. Ruta angustifolia is a natural resource which was reported to possess anti-HCV activity. Ribavirin is an antiviral agent used to treat several virus infections, either DNA or RNA. Ribavirin was known to inhibit HCV infection by regulated immune system in host cells and interfering the replication of HCV by inhibit HCV RdRp. Objective: The current study evaluated the combination treatment of R. angustifolia extracts and ribavirin by in vitro culture cells of Huh 7it. Method: The study was conducted under an invitro cell culture of Huh 7it and infected with JFH1a. Result: The result demonstrated an enhancement effect of the extract by increasing the anti-HCV activity 3.5-fold higher compared to ribavirin alone. The 50% inhibitory concentration of ribavirin by single treatment was 10.43 ± 0.18 µg/mL, while in combination with Ruta angustifolia extract was 2.80 ± 0.03 µg/mL. Further analysis of the combination by CompuSyn software mediated a synergistic effect among the combination with a combination index value of 0.691. Conclusion: These results suggested that combination of Ribavirin and Ruta angustifolia should be considered in developing anti-hepatitis C virus agents.